Short Fatigue Crack Behavior of LZ50 Axle Steel under Rotating-Bending Cyclic Loading - Yang, B.; Dai, S.; Wu, Y.Y.; Liao, Z.; Liang, S.; Xiao, S.N. (Проблемы прочности, 2018)
The short fatigue short crack replica tests using LZ50 axle steel hourglass-shaped specimens of were carried out under rotating-bending cyclic load. Seven sets of effective test data were obtained. The analysis demonstrated that short fatigue cracks generally originate in ferrite grains or on their boundaries, and then short cracks start propagating, which is strongly influenced by the microstructure of the material. The crack growth rate increases serratically, followed by its decrease double-fold because of the limit of ferrite grain boundaries and the banded pearlite structure. Based on the three principles of the best fit, which include the overall fitting effect, correlation with fatigue physics, and safety of residual strength prediction, the statistical evolution of the dominant effective short fatigue crack length and life share were analyzed. The statistical results show that the minimum value distribution exhibit the best fit of the dominant effective fatigue short crack length and the life share. The short fatigue crack growth model, which includes various microstructure barriers, provides a good fitting result and reflects the cyclic effect of the microstructure on the short fatigue crack behavior